An optical fiber humidity sensor based on femtosecond laser micromachining Fabry-Perot cavity with composite film. (June 2022) - Zhang, Zhaoxu; Gong, Huaping; Yu, Changgui; Ni, Kai; Zhao, Chunliu
Highlights: The effect of the hole perforated on the Fabry-Perot cavity by femtosecond laser on the humidity performance of the proposed sensors is studied for the first time. The proposed sensor has a high humidity sensitivity of −525 pm/%RH. The influence of film thickness on the humidity sensitivity of the sensor is discussed. The humidity characteristics of the proposed sensors with different mixture ratios of HA/PVA composite are investigated. The proposed sensor has the advantages of simple fabrication, good robustness and high stability. Abstract: An optical fiber relative humidity(RH) sensor based on femtosecond laser micromachining Fabry-Perot cavity with composite film is proposed. The effect of the hole perforated on the Fabry-Perot cavity by femtosecond laser on the humidity performance of the sensors is studied for the first time. And the humidity characteristics of the sensors with different mixture ratios of HA/PVA composite are investigated. The influence of film thickness on the humidity sensitivity of the sensor is also discussed. The sensor perforated the hole of 40 μm with the mixture ratios of 1:2 HA/PVA and the film thickness of 20 μm has the best performance. The sensor has a linear response to humidity with the linearity of 99.5% and the sensitivity is up to −525 pm/%RH, within the relative humidity range of 35–85%, under the room temperature of 25 °C. The response time is as short as 2 s. The sensor has the advantages of simple fabrication, high sensitivity and high stability.